2017
DOI: 10.36095/banxico/di.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

The International Bank Lending Channel of Monetary Policy Rates and QE: Credit Supply, Reach-for-Yield, and Real Effects

Abstract: La serie de Documentos de Investigación del Banco de México divulga resultados preliminares de trabajos de investigación económica realizados en el Banco de México con la finalidad de propiciar el intercambio y debate de ideas. El contenido de los Documentos de Investigación, así como las conclusiones que de ellos se derivan, son responsabilidad exclusiva de los autores y no reflejan necesariamente las del Banco de México.The Working Papers series of Banco de México disseminates preliminary results of economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Banks' lending incentives may be different during this period due to the large quantities of reserves they hold. Still, it is an interesting finding in the domestic context, seeing as Morais et al (2017) and Temesvary et al (2018) found some evidence of the bank credit channel in U.S. banks' lending in foreign countries.…”
Section: Alternative Specificationsmentioning
confidence: 94%
“…Banks' lending incentives may be different during this period due to the large quantities of reserves they hold. Still, it is an interesting finding in the domestic context, seeing as Morais et al (2017) and Temesvary et al (2018) found some evidence of the bank credit channel in U.S. banks' lending in foreign countries.…”
Section: Alternative Specificationsmentioning
confidence: 94%
“…Our paper speaks to the literature on the economic effects of commodity price changes in developing countries and makes a contribution on several fronts. We expand the literature on the international transmission of macroeconomic shocks through the bank lending channel (Baskaya et al 2017;Cetorelli and Goldberg 2011;Ivashina, Scharfstein, and Stein 2015;Morais et al 2019;Ongena, Peydró, and Van Horen 2015;Peek and Rosengren 1997;Schnabl 2012) by focusing on commodity prices. We bring to this literature a unique administrative data on the universe of loan applications for a developing country.…”
Section: Figurementioning
confidence: 99%
“…important role in the transmission of shocks, both domestic and external, to economic activity. While there is no dearth of studies on the international transmission of shocks through the banking sector in the context of advanced and emerging market economies (Cetorelli and Goldberg 2011;De Haas and Van Horen 2013;Ivashina, Scharfstein, and Stein 2015;Morais et al 2019;Ongena, Peydró, and Van Horen 2015;Schnabl 2012), there is little evidence on the role of banks in the transmission of global shocks to developing countries, possibly because of low levels of global financial integration of banks in these countries. However, the transmission of international shocks through bank lending could have important effects on the real economy in developing countries, where equity and bond markets are underdeveloped and banks are an important source of finance for domestic firms.…”
mentioning
confidence: 99%
“…The results indicate that the positive association between the unconventional monetary policy and the industry-level total output and total wages and salaries becomes somewhat stronger. 5 Following Morais et al (2019), I also use the annual growth rate in total assets of the Federal Reserve over GDP as an alternative measure of unconventional monetary policy. The results presented in Table 14 confirm that the positive growth rate in large-scale asset purchases corresponds with subsequent increases in industry-level total output and total wages and salaries.…”
Section: Sensitivity Testmentioning
confidence: 99%